(untitled) (Swiss Medical Weekly, 2017)
Takotsubo syndrome (TTS) was first described in 1991 as a rare, spontaneous and completely reversible left ventricular regional systolic dysfunction. Today the incidence of TTS is estimated at 2% in patients with an initial diagnosis of acute coronary syndrome (ACS). Notably, the incidence can be as high as 5.9 to 7.5% in female patients. TTS occurs predominantly in postmenopausal women, but both sexes may be affected, at any age. Acute chest pain or dyspnoea is a characteristic symptom of TTS, but initial presentation can also include more severe disease manifestation such as acute heart failure with pulmonary oedema or haemodynamic instability, especially in an in-hospital setting. It is now known that TTS is triggered by not only emotional, but also physical stressors, or a combination of both. Although apical ballooning is the most frequent and typical finding on imaging, different types of TTS have been described, including the midventricular, basal and focal forms. The acute phase of TTS may be complicated by cardiogenic shock, left ventricular outflow tract obstruction, severe mitral valve regurgitation, embolisation of ventricular thrombi and life-threatening ventricular arrhythmias. Furthermore, although originally thought to be a completely reversible condition, the long-term prognosis of TTS is not entirely positive, with a major adverse cardiac and cerebrovascular event (MACCE) rate of 9.9% reported in the InterTAK Registry, the largest series of patients with TTS. The exact aetiology of TTS remains unknown, there are no current treatment guidelines and differential diagnosis from the more frequent ACS entities remains particularly challenging. Overall, TTS remains a poorly understood and under-diagnosed disease, sometimes disguised in clinically atypical presentations. This review presents different TTS cases to illustrate that TTS is a heterogeneous disease.